1996
DOI: 10.3109/09537109609023571
|View full text |Cite
|
Sign up to set email alerts
|

Plasma albumin and platelet function: relevance to atherogenesis and thrombosis

Abstract: Two papers published in this journal(1,2) during the past year remind us that plasma albumin concentrations can influence platelet function. These publications, together with epidemiological evidence showing that low plasma concentrations of albumin predict mortality from cardiovascular disease(3,4) have prompted this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
99
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 114 publications
4
99
2
1
Order By: Relevance
“…Serum albumin is a main inhibitor of platelet activation and aggregation and an important mediator of platelet-induced coronary artery narrowing. 14,15 Lower SA concentrations may be associated with more activated platelets leads to more extent and complex CAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum albumin is a main inhibitor of platelet activation and aggregation and an important mediator of platelet-induced coronary artery narrowing. 14,15 Lower SA concentrations may be associated with more activated platelets leads to more extent and complex CAD.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Additionally, SA is an important inhibitor of platelet activation and aggregation and an important mediator of platelet-induced coronary artery narrowing. 14,15 Moreover, one of the most important functions of SA is its antioxidant activities. 16 It is well known that lower concentrations of SA can predict increased morbidity and mortality risks in a range of cardiovascular diseases including ACS.…”
Section: Introductionmentioning
confidence: 99%
“…6 The role of low plasma albumin levels in atherogenesis and thrombosis has been discussed. 7 Hypoalbuminemia increases plasma levels of lipoprotein (a) and fibrinogen as well as arachidonic acid metabolites, platelet aggregability, and blood viscosity, all of which contribute to the risk of cardiovascular disease. 7 Albumin may also inhibit the proaggregatory effect of fibrinogen on platelets.…”
mentioning
confidence: 99%
“…7 Hypoalbuminemia increases plasma levels of lipoprotein (a) and fibrinogen as well as arachidonic acid metabolites, platelet aggregability, and blood viscosity, all of which contribute to the risk of cardiovascular disease. 7 Albumin may also inhibit the proaggregatory effect of fibrinogen on platelets. 8 Moreover, various epidemiologic studies have reported associations between cardiovascular disease and albumin.…”
mentioning
confidence: 99%
“…15 Albumin may have antioxidant as well as other properties that may decrease the risk of vascular disease. 8,10,[16][17][18] There are some data from Asian patients that bilirubin might have a protective role for hemorrhagic stroke in men but not women (reviewed in 3,4 ). Seeing that the 3 main causes of death are heart disease, cancer, and stroke, if there is really a relationship with overall death but not with CVD, CHD of MI as Horsfall et al's data 11 imply, because several of the large studies included in the recent meta-analyses of stroke do not address hemorrhagic stroke specifically (possibly owing to lack of information about this type of stroke in many of the studies), it would appear unwise to write off a role of bilirubin in hemorrhagic stroke.…”
mentioning
confidence: 99%